Genetic characterization and clonal analysis of carbapenemase-producing Escherichia coli and Klebsiella pneumoniae from canine and human origins - Khine, Nwai Oo; Shah, Asad Ali; Chatsuwan, Tanittha; Yindee, Jitrapa; Supimon, Natthapong; Saenkankam, Imporn; Hampson, David John; Prapasarakul, Nuvee (Frontiers in Veterinary Science, 2024)
IntroductionCarbapenem-resistant Enterobacterales (CRE), particularly carbapenemase-producing Escherichia coli and Klebsiella pneumoniae, pose a significant global health challenge due to their resistance to last-resort antibiotics. This study investigates the genetic characteristics and clonal relationships of CRE isolated from canine and human clinical samples in Bangkok to understand potential interspecies transmission.MethodsFifty-two CRE isolates were collected from 477 clinical samples from dogs and humans at Chulalongkorn University between 2017–2021. Bacterial species were identified using MALDI-TOF, and antimicrobial resistance was confirmed through broth microdilution testing. Genetic analyses included plasmid replicon typing, multilocus sequence typing (MLST), whole genome sequencing (WGS), and pulsed-field gel electrophoresis (PFGE) to assess resistance genes and clonal relatedness.ResultsCRE isolates from both species exhibited genetic variability with high ARG counts, particularly in human isolates. MLST identified ST410 in most E. coli isolates from both dogs and humans, and IncFIA/IncFIB plasmids were predominant among blaNDM-positive isolates. PFGE patterns and SNP analysis showed no clonal relationship between canine and human isolates, suggesting independent acquisition pathways for CRE in the two hosts.DiscussionThe study highlights the absence of direct clonal transmission between canine and human isolates but reveals overlapping sequence types and plasmid types. The findings underscore the potential for interspecies transmission under certain conditions, emphasizing the importance of a One Health approach for monitoring CRE in both human and animal populations.